Adsorption of lead and chromium ions from electroplating wastewater using plantain stalk modified by amorphous alumina developed from waste cans - E. O. Ajala; M. O. Aliyu; M. A. Ajala; G. Mamba; A. M. Ndana; T. S. Olatunde (Scientific Reports, 2024)
Abstract Waste beneficiation is key to environmental protection and the realisation of a circular economy. Herein, amorphous alumina (a-Al2O3) derived from aluminium waste cans (AWC) was used to modify plantain stalk as an adsorbent for sequestration of lead (II) and chromium (VI) ions from electroplating wastewater. Raw plantain-stalk (RPS) and amorphous-alumina modified plantain stalk (APS) developed as adsorbents were characterised using various equipment such as x-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and Brunauer–Emmett–Teller (BET). The FTIR revealed that the adsorbents are rich in functional groups that could promote the adsorption process which includes carboxyl, hydroxyl, and aliphatic groups. Also, the BET analysis showed a substantial increase in the surface area of APS (174.448 m2/g) compared to that of RPS (40.531 m2/g) which could be due to the effect of modification by the a-Al2O3. The batch adsorption studies revealed that the APS achieved 99.38% and 98.33% removal of Cr(VI) and Pb(II), respectively, which is superior to RPS adsorption efficiency. Also, the estimated and experimental data for the APS compared well under all the kinetic models studied with R2 > 0.88. This suggested that chemisorption is the most plausible adsorption mechanism of Cr(VI) and Pb(II) onto the APS. Further analysis showed that the Cr(VI) and Pb(II) adsorption followed the Langmuir model with the RL value of 0.038 and 0.999, respectively, which indicated that the two metal ions were effectively adsorbed onto the APS. Therefore, this work demonstrated that the modification of plantain-stalk with amorphous-alumina derived from AWC enhanced the characteristics of the APS and favoured its adsorption of the selected heavy metals.